Controlled drug delivery systems for cancer based on mesoporous silica nanoparticles - Iturrioz-Rodríguez N (Dove Medical Press, 2019)
Nerea Iturrioz-Rodríguez,1 Miguel A Correa-Duarte,2,3 Mónica L Fanarraga11Nanomedicine Group, University of Cantabria – IDIVAL, Santander, 39011, Spain; 2Department of Physical Chemistry, Center for Biomedical Research (CINBIO), Southern Galicia Institute of Health Research (IISGS), Vigo 36310, Spain; 3Biomedical Research Networking Center for Mental Health (CIBERSAM), Universidade de Vigo, Vigo 36310, SpainAbstract: The implementation of nanotechnology in medicine has opened new research horizons particularly in the field of therapeutic delivery. Mesoporous silica particles have emerged as biocompatible drug delivery systems with an enormous potential in the treatment of cancer among many other pathologies. In this review, we focus on the unique properties of these particles as chemotherapy delivery carriers. Here, we summarize the general characteristics of these nanomaterials – including their physicochemical properties and customizable surfaces – different stimuli that can be used to trigger targeted drug release, biocompatibility and finally, the drawbacks of these types of nanomaterials, highlighting some of the most important features of mesoporous silica nanoparticles in drug delivery.Keywords: nanocarrier, drug release, targeted drug delivery, biocompatibility, biodegradability, tumor